Flipped Classroom in Mutation Chapter Learning: Studies in Student Learning Outcomes - Risna, Andi; Saleh, Andi Rahmat; Nurhayati B (Indonesian Journal of Mathematics and Natural Science Education, 2023)
Flipped Classroom is a learning innovation that is in line with developments in time and technology. This research aims to see the effect of the flipped classroom learning model on students' biology learning outcomes, especially the concept of mutation. This research is an experimental research with the Quasy Experiment Design type of research which aims to determine the effect of the flipped classroom learning model on student learning outcomes in the mutation chapter at SMAN 9 Makassar. The independent variable of this research is the application of the flipped classroom learning model and the conventional learning model, while the dependent variable is the students' learning outcomes on mutation chapter. The population of this research is all students in class The research data was obtained by giving a test of learning outcomes on mutation material in the form of a pretest and posttest. The data analysis technique was carried out using covariate analysis (Anakova). Based on the analysis results, P = <0.001 is smaller than α = 0.05. It can be concluded that the application of the flipped classroom learning model has a significant effect on the learning outcomes of class XII MIA SMAN 9 Makassar students on mutation chapter. Kata Kunci: flipped classroom, hasil belajar, konvensional, model pembelajaran, mutasi.